Exploring Politicized Trust in a Racially Diverse Computer Science Classroom. Issue 4 (4th July 2019) - Vakil, Sepehr; de Royston, Maxine McKinney
ABSTRACT: Over the past decade, abroad range of policymakers, corporations, educators, and scholars in the United States have catapulted computer science (CS) education from the sidelines to the center of K-12 public education discourse. While calls for CS education are often framed in terms of national and economic competitiveness, there is a growing interest amongst equity scholars in curricular interventions that directly engage the ethical and sociopolitical issues surrounding CS and its role in society. Yet, less attention has been given to how sociocultural dynamics of classrooms play a mediating role in these spaces. Drawing on video data from an equity-oriented CS classroom, we argue aconflict that arose during design activities was rooted in alack of trust and solidarity between students. Ultimately, we make the case that in addition to curricular innovations, equity efforts in CS education must prioritize the cultivation of positive student relationships.